Diagnosis and treatment outcomes of Cushing’s disease during pregnancy - Sridharan, Kalyani; Sahoo, Jayaprakash; Palui, Rajan; Patil, Milind; Kamalanathan, Sadishkumar; Ramesh, A. S.; Kubera, N. S. (Pituitary, 2021)
Purpose We report a case of a pregnant woman with Cushing’s disease (CD) and performed a systematic review of literature on diagnosis, treatment, maternal and fetal outcomes of CD in pregnancy. Methods A PubMed search was performed for manuscripts in English language from inception till June 2020. Cases of CD with hypercortisolism during pregnancy were included and categorized into three groups based on treatment received. Data on diagnostic modalities, CD remission, materno-fetal outcomes were analysed. Results Fifty-five patients of CD with 62 pregnancies were analysed. 24-h urinary free cortisol(UFC) was elevated by a mean of 5.4 ± 4.2 fold upper limit of normal non-pregnant level. 12/19 (63.1%) CD patients had more than threefold elevation of UFC measured during pregnancy. Mean midnight serum cortisol was 753.7 ± 270.5 nmol/l. At a midnight serum cortisol cut off of 440 nmol/l, 15/16 patients were correctly identified as CD. 23.2% underwent trans-sphenoidal surgery (group 1), 16.1% received only medical treatment (group 2) while 60.7% received no treatment (group 3) during pregnancy. Remission rates for CD in groups 1 and 2 were 76.9% and 77.8%, respectively. Adverse maternal and fetal outcomes were seen in 53.9% and 59.3% of the patients, respectively and were not significantly different between groups, although, lesser live births and greater pregnancy losses were seen in group 3. Conclusion Midnight serum cortisol had better sensitivity than UFC for diagnosing hypercortisolism due to CD during pregnancy. In general, CD should be treated during pregnancy in order to optimize maternal and fetal outcomes as a trend towards increased live births is seen in treated subjects.